VIEWER COMPUTER CLOCK TO SEVEN SEGMENT - Vetnam Siahaan; Jalinas Jalinas, Skom, MM (Jurnal Sistem Komputer, 2000)
This allows the viewer hours of computer users can set the tim e when the computer operates. Based on my test results from the tools that I make, the hours are displayed on seven segment equals the value of the existing hours in memory. From the economical aspect of this series is less favorable, when compared with th e manufacture of substitutes for regular hours.Â